PERAN KANTOR URUSAN AGAMA DALAM PENCATATAN ISBAT NIKAH (Studi Di Kantor Urusan Agama Kecamatan Singkawang Tengah) - Nasirin, Nasirin; Marluwi, Marluwi; Ardiansyah, Ardiansyah (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
The aims of this study were to determine: 1) the procedure for registering underhand marriages at KUA Singkawang Tengah; 2) The role of the Central Singkawang KUA in an effort to minimize underhanded marriages in the community in Central Singkawang. Researchers used qualitative research methods with field research and normative-empirical approaches. The primary data sources are in the form of interviews with the head of the Central Singkawang KUA whose subject has been determined, secondary data in the form of books and other supporting documents that can strengthen this research. The data collection techniques chosen in this study were observation, interviews, and documentation. Meanwhile, by using data reduction analysis techniques, data presentation, and drawing conclusions. The technique of checking the validity of the data in this study uses source triangulation. It can be concluded: 1) The procedure for registering illegal marriages at KUA Singkawang is in the middle of having to do a marriage certificate first at the Religious Courts and then husband and wife also attach the administrative requirements needed to register marriages under the hands at KUA then a book can be published. married husband and wife; 2) The role of KUA in minimizing underhanded marriages is in the form of providing excellent marriage registration services and providing counseling to the public about the importance of marriage registration and the facilities offered.